THE EFFECT OF HEALTH EDUCATION USING DEMONSTRATION METHOD ON THE SKILL OF PERFORMING BREAST SELFT-EXAMINATION (BSE) AMONG FEMALE ADOLESCENTS AT MA PONDOK PESANTREN KULNI CIKANDE. - lindawati; Nadya choirunnissa (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2025)
Breast self-examination (BSE) is an early detection method for breast cancer that is performed independently and regularly. By observing and palpating the breasts, individuals may identify early changes that could indicate potential health problems. BSE is an important preventive measure, particularly for female adolescents, as it helps foster early awareness of reproductive health. To determine the effect of health education using the demonstration method on breast self-examination (BSE) skills among female adolescents at MA Pondok Pesantren Kulni.This study employed a pre-experimental design with a one-group pre-test–post-test approach. The sampling technique used was total sampling (census sampling), involving 49 respondents. Data were collected using an observation checklist. The Wilcoxon test showed a p-value of 0.000, which was lower than the significance level of 0.05, indicating a statistically significant difference. The findings indicate that health education using the demonstration method had a significant effect on BSE skills among female adolescents.